Origin and mechanisms of volume swelling in borosilicate glass during femtosecond-laser-microforming - Skiba, Marina; de Ligny, Dominique; Lasagni, Andrés Fabián; Bliedtner, Jens (Results in Materials, 2026)
This study investigates the mechanisms of ablation-free microforming of borosilicate glass using Raman spectroscopic structural analysis. The glass sample is irradiated by a femtosecond-laser scanning process, inducing surface topography changes and a volume change within the irradiated region. Raman measurements were performed in the central volume of the sample. Raman mapping and line scans are compared with reference samples obtained by controlled heat treatments (annealing), thereby enabling both qualitative and quantitative evaluations of the laser-induced structural modifications. Correlations between Raman signal and glass density allow determining the origin of the local volume changes. High cooling rates during microforming correlate with a Raman shift toward higher wavenumbers (Δ ∼6 cm−1) and the associated decrease in density (Δ ∼0.5 %). From these relationships, the density distribution within the microformed region is derived and fully explains the volumetric change.
CRIS-Team Scopus Importer:2026-04-24
Keywords: Borosilicate glass; Material modification; Microforming; Raman spectroscopy; Ultrashort laser pulses